The Implementation of Character-based Curriculum to Improve the Akhlakul Karimah of Students in Alam Elementary School Bandung - Nurwataniah, Nurwataniah; Hasan, Said Hamid; Susilana, Rudi (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
The base of the research are the facts that show weak character on students, it causes various problems such as violence in school, porn, drugs, free sex, student brawls and also various social problems in the community. This study aims to review the implementation of character-based curriculum to improve akhlakul karimah. This study uses qualitative approach and case study method. The data collection techniques used in this study are observation, interwiew, and document study. The result of the study shows the planning of character-based curriculum to improve akhlakul karimah of the students in Alam Elementary School Bandung are: program planning, planning based on KTSP planning, develop learning program based on school’s vision, mission, and goals in accordance with the philosophy of Alam Elementary School. This study uses both direct and indirect learning for its learning implementation. Classroom management which centered on students by using various approach are: contextual learning, learning by doing, inquiry and also incidental based on the students’ mood. The use of nature as the laboratory is the students learn to blend directly with the nature and the nature as the media and study resources. The implementation of learning process includes preliminary activities, main activities, and closing activities. The evaluation is done comprehensively which is provided in the report (groovy report), narrative reports, and number reports. Akhlakul karimah evaluation is done by daily monitoring. Lessons evaluation is carried out through formative evaluation and summative evaluation. Formative evaluation is carried out through exercises.